Being a good or a just teacher: Which experiences of teachers' behavior can be more predictive of school bullying?. Issue 1 (30th July 2017) - Donat, Matthias; Knigge, Michel; Dalbert, Claudia
Abstract : In two cross‐sectional questionnaire studies with N = 2, 931 German students, aged between 12 and 17 years ( M = 14.1, SD = 0.5), we investigated the relation between students' bullying behavior and their personal belief in a just world (BJW). We considered students' personal experience of teacher justice as a possible mediator in this relation and investigated whether the students' experiences of their teachers' classroom management explained bullying behavior in addition to personal BJW and teacher justice, while statistically controlling for sex and school type. In both studies, multilevel modeling results showed that the more students endorsed personal BJW and the more they evaluated their teachers' behavior toward them personally as being just, the less likely they were to report that they bullied others. The students' personal experience of teacher justice mediated the association of personal BJW with bullying. Furthermore, the students' personal experience of classroom management significantly predicted bullying in addition to personal BJW and teacher justice. The observed relations were mainly significant at the individual level. The pattern of results persisted when we controlled for school type and when we considered student sex as a moderator. We discussed the adaptive functions of BJW and implications for future school research and practice.